2016
DOI: 10.1016/j.jaad.2015.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of recalcitrant adult alopecia areata universalis with oral azathioprine

Abstract: I), which are slightly lower than the present results. Interestingly, the reported rate of adverse effects in these studies (10%-41%) was similar to the present rate (33%); in general, the adverse effects were mild and transient. The present study is limited by the absence of a control group.In conclusion, treatment with PCT-OD at a dosage of 0.1 mg/kg/day biweekly is a potential therapeutic option for adults with AT/AU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
1
25
0
1
Order By: Relevance
“…Previous studies described the efficacy of MTX, alone or in combination with corticosteroids, for the treatment of extensive forms of AA with successful response in both adult and paediatric populations. [4][5][6] Other studies tested AZA alone 7,8 in the treatment of AA, with clinical outcomes and follow-up almost comparable to our experience. The association AZA plus MTX has never been experienced before in the treatment of severe forms of AA; however, the therapeutic concept has already been described by our group in adult patients with severe atopic dermatitis.…”
Section: Editorsupporting
confidence: 71%
See 1 more Smart Citation
“…Previous studies described the efficacy of MTX, alone or in combination with corticosteroids, for the treatment of extensive forms of AA with successful response in both adult and paediatric populations. [4][5][6] Other studies tested AZA alone 7,8 in the treatment of AA, with clinical outcomes and follow-up almost comparable to our experience. The association AZA plus MTX has never been experienced before in the treatment of severe forms of AA; however, the therapeutic concept has already been described by our group in adult patients with severe atopic dermatitis.…”
Section: Editorsupporting
confidence: 71%
“…This innovative and low-cost approach could be considered in the therapeutic arsenal against refractory forms of AA, in the context of the clinical development of JAK1 and JAK2 inhibitors in the treatment of severe AA. [3][4][5][6][7][8][9][10]…”
Section: Editormentioning
confidence: 99%
“…Additionally, 66% showed no signs of relapse after treatment discontinuation; the remaining patients relapsed after 2.5 months. 100,101 Although research on this treatment is scarce, this is another systemic therapy that can be considered for recalcitrant AA. However, the risk of systemic side-effects should be considered.…”
Section: Azathioprinementioning
confidence: 99%
“…Data from a larger multicentre observational review of treatments for alopecia in Spain identified 15 of 132 patients who were treated with MTX; five in combination with prednisolone and 10 with MTX monotherapy. 27 Three on combination therapy responded, and none of those on MTX alone, although six were reported as partial responders (< 75% regrowth).…”
Section: Mtx Plus Prednisolonementioning
confidence: 91%